2001
DOI: 10.1002/app.1977
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of lipase on poly(N‐vinyl‐2‐pyrrolidone‐co‐styrene) hydrogel

Abstract: ABSTRACT:Lipase from Candida rugosa was immobilized by entrapment while polymerizing a poly(N-vinyl-2-pyrrolidone-co-styrene) [poly(VP-co-ST)] hydrogel using ethylene dimethacrylate (EDMA) as the crosslinking agent. The immobilized enzymes were used in the esterification reaction of oleic acid and butanol in hexane. The activities of the immobilized enzymes and the leaching ability of the enzyme from the support with respect to the different compositions of the hydrogels were investigated. The thermal, solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Compared with conventional chemical synthesis from alcohols and carboxylic acids using mineral acids as a catalyst, the use of enzymes, such as lipases, as biocatalysts to produce these high value-added fatty acid esters in organic media offers significant advantages (Klibanov 1986;Dordick 1989;Malcata et al 1990;Bornscheuer 1995;Yahya et al 1998;Basri et al 2001). Various features of reaction selectivity of lipases are modulated by exogenous factors such as type of organic solvent, choice of co-substrates/reactants, water activity, pH, temperature and immobilization support (Jensen et al 1990;Bornscheuer & Yamane 1994;Klein et al 1997;Rhee & Kwon 1998;Lee & Parkin 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional chemical synthesis from alcohols and carboxylic acids using mineral acids as a catalyst, the use of enzymes, such as lipases, as biocatalysts to produce these high value-added fatty acid esters in organic media offers significant advantages (Klibanov 1986;Dordick 1989;Malcata et al 1990;Bornscheuer 1995;Yahya et al 1998;Basri et al 2001). Various features of reaction selectivity of lipases are modulated by exogenous factors such as type of organic solvent, choice of co-substrates/reactants, water activity, pH, temperature and immobilization support (Jensen et al 1990;Bornscheuer & Yamane 1994;Klein et al 1997;Rhee & Kwon 1998;Lee & Parkin 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] They have been proven to enhance the stability of enzymes against heat, pH, and organic solvents. [21][22][23][24][25][26] Recently, a Ni 2+ -poly(2-acetamidoacrylic acid) (Ni 2+ -PAAA) hydrogel system was introduced for purication and immobilization of histidine-tagged proteins. [27][28][29] In addition, PAAA hydrogels have been utilized in diverse biotechnological applications on account of their water-absorbing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In addition, PAAA hydrogels have been utilized in diverse biotechnological applications on account of their water-absorbing capacity. 21,22,24 Radiofrequency (RF) waves or currents have been intensively studied as a way to deliver heat or to activate the molecules for various applications including food technology 30,31 and inducing hyperthermia in medical treatment. 32,33 Although it was reported that acetylcholinesterase (AChE) in neuroblastoma cells showed enhanced activity when exposed to RF radiation of 147 MHz from 7.0 to 7.5 hours, 34 the effect of RF on the enzyme was not directly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization of enzymes within the hydrogel microparticles provides a higher density of the enzyme than can be achieved via surface immobilization and a protective environment for the enzyme resulting in maintaining the stability of the enzyme due to the properties of hydrogels such as hydrophilicity, biocompatibility, permeability and highly cross-linked networks [10,11]. Although there are many researchers utilizing hydrogels as a substrate for enzyme immobilization [12][13][14], most of them use large size of hydrogels and few studies have been reported preparing enzyme-entrapped hydrogel microparticles.…”
Section: Introductionmentioning
confidence: 99%